Occlusal Plane and Skeletal Changes After Cervical Headgear Treatment With and Without Lower Utility Arch in Class II Growing Patients. Issue 3 (May 2021) - Sambataro, Sergio; Bocchieri, Salvatore; Fastuca, Rosamaria; Giuntini, Veronica; Fiorillo, Luca; Cicciù, Marco; Caprioglio, Alberto
Abstract : Abstract: The purpose of this study was to investigate skeletal and dental changes affecting occlusal plane inclination after cervical headgear treatment with and without lower utility arch. In order to distinguish the orthodontic changes from natural growth a control group was employed. The sample of this study consisted by 20 Class II subjects (10 males, 10 females; mean age 8.54) treated by using cervical headgear, 19 class II children (19 males, 9 females; mean age 8.64) treated with cervical headgear and utility arch, and 21 Class II patients (11 males, 10 females; mean age 8.41) who had no therapy. Lateral head films were studied for all the patients before treatment (T1) and after therapy (T2) for all the treated groups and at the beginning and at the end of observational period for the control group; cephalometric analysis was carried out in order to seek for the modifications between time points and between groups. Means and standard deviation have been analyzed for all the groups. In order to compare the modification between the time points within the same group the ANOVA test was applied. The ANOVA test was used to compare the mean differences (T2-T1) of 3 groups. The study revealed that there were significant changes in occlusal plane inclination after the different treatment modalities employed instead control group. The treatment with cervical headgear and utility arch is more effective than cervical headgear alone in lowering occlusal plane posteriorly when it is compared with controls. Abstract : Supplemental Digital Content is available in the text